Yogurt-like Product from Fermented Maize: Part II: Quality Improvement - Nguyen, Tien Cuong; Nguyen, Van Gioi; Nguyen, Thi Hoai Duc; Luong, Hong Nga (Old Journal, 2018)
This study aimed to develop the method for stabilising the quality of fermented maize-based product by some technical solution. Three homogenisation pressures were applied (150, 200 and 250 bar). Then suspensions were mixed with xanthan and gellan gums separately with different concentrations ranging from 0.1 to 0.2%. Two flavours were tested: corn and milk flavours at concentration between 0.1 to 0.15%. The sediment height, pH, acidity, viscosity and sensory attributes were followed during storage time until 1 month. Results showed that the use of 250 bar of homogenisation pressure and 0.2% of gellan gum and with mixed corn-milk flavours at 0.1% gave the best quality of product. During one month of storage, no decantation was observed; the biochemical and sensory characteristics were maintained (pH≈4, acidity